(untitled) (Comprehensive Journal of Science, 2026)
An x-ray in regards to the electromagnetic spectrum, refers to a form of high-energy electromagnetic radiation, characterised by a short wavelength and it’s ability to pass through opaque materials, which makes it ideal in medical imaging to view the internal structures of the human body. Their ability to penetrate soft tissue and while being absorbed by denser materials such as bones, allow contrast-based images to be produced as scans for medical research and diagnoses. There is a theoretical aspect of the role of x-rays in medical imaging, how they interact with matter within the human body, how the imaging process operates and is conducted and how this applies to the management of technological and safety systems to ensure efficiency in it’s usage. Thoroughly, wave particle behaviour and attenuation is connected to detection of anomalies and structures in the human body, further reiterating how high energy waves are able to reveal internal anatomy in clinical contexts.